HUMAN RESOURCES DATA ANALYSIS FOR DECISION MAKING: THE USE OF DATA ANALYTICS AND ARTIFICIAL INTELLIGENCE (AI) IN FORECASTING HUMAN RESOURCE TRENDS, TALENT MANAGEMENT, AND EDUCATOR PERFORMANCE - Ani Zulaikhah; Novilia; Nopiliasari; Nelly; Neta Dian Lestari; Ahmad Zulinto (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This research explores the utilization of data analytics and artificial intelligence in strategic decision-making for educational human resource management. Employing a qualitative approach through library research methodology, this study analyzes literature from internationally indexed journals, books, and relevant research reports. Findings reveal that implementation of predictive analytics and machine learning algorithms enhances the accuracy of educator demand forecasting by 35 percent, talent management efficiency by 60 percent, and performance productivity by 32 percent. Analytical technology enables educational institutions to make evidence-based decisions in recruitment, professional development, and performance evaluation. However, implementation in Indonesia faces challenges including technological infrastructure limitations, digital competency gaps, and organizational cultural resistance. Gradual adoption strategies with capacity development investments, multi-stakeholder collaboration, and supportive institutional policies become key success factors for digital transformation. This research contributes to technology-based human resource management literature within the Indonesian educational context.